2018
DOI: 10.1002/ppul.24165
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in U.S. infants with cystic fibrosis from 2001 to 2012

Abstract: Background All 50 United States implemented newborn screening (NBS) for cystic fibrosis (CF) by 2010. The purpose of this study was to evaluate trends over the decade when NBS became universal to determine current rates of malnutrition, stunting, and infection rates in U.S. infants with CF. Methods Annual data were obtained on infants with CF up to 24 months of age diagnosed between 2001 and 2010 in the CF Foundation Patient Registry (CFFPR), in both the years of and after diagnosis, including method of diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Other factors such as improved infection control, airway clearance techniques and antibiotic stewardship were not evaluated in this study but may have also contributed to the change in infection prevalence. These factors clearly represent a general improvement in care, in line with current international guidelines, that are likely to have contributed to the decrease in prevalence of bacterial pathogens in ours and other cohorts (29)(30)(31)33) 11 S. aureus is often considered to be the first pathogen cultured from respiratory secretions in young patients with CF (1-3) with an overall reported prevalence of 30% to 70% (2,8,9). In our cohort, the median age of first infection with S. aureus was not significantly different from that of P. aeruginosa and the overall prevalence of S. aureus lower airway infection was only 11%.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Other factors such as improved infection control, airway clearance techniques and antibiotic stewardship were not evaluated in this study but may have also contributed to the change in infection prevalence. These factors clearly represent a general improvement in care, in line with current international guidelines, that are likely to have contributed to the decrease in prevalence of bacterial pathogens in ours and other cohorts (29)(30)(31)33) 11 S. aureus is often considered to be the first pathogen cultured from respiratory secretions in young patients with CF (1-3) with an overall reported prevalence of 30% to 70% (2,8,9). In our cohort, the median age of first infection with S. aureus was not significantly different from that of P. aeruginosa and the overall prevalence of S. aureus lower airway infection was only 11%.…”
mentioning
confidence: 76%
“…Another major finding in our study is the significant decrease in the prevalence of lower airway P. aeruginosa, S. aureus and H. influenzae infections during the study period. Due to the observational nature of the study, causality cannot be assessed for this observation, but a similar decrease in incidence and prevalence of P. aeruginosa infections in older patients with CF, and recently also in infants diagnosed after newborn screening, has previously been reported (29)(30)(31). Our study focuses on a young cohort of children, mostly naïve to previous infections and represents most of the children in the two centres with comprehensive follow up from diagnosis following newborn screening and direct evaluation of lower airway pathogens (13).…”
mentioning
confidence: 91%
“…The nutritional status of all CF patients has been improving over the last couple of decades, secondary to many factors including early detection through newborn screening (NBS). As NBS became widely available from 2001 to 2010, the percentage of infants with weight and length z-scores less than À2 decreased from 30% of infants to 12% [3]. Weight percentiles at all ages have improved over the last decade, but less improvement has been seen in height percentiles ( Fig.…”
Section: Nutrition and Growth In Cystic Fibrosismentioning
confidence: 98%
“…The effect of newborn screening on outcomes through age 2, from 2001 to 2012, demonstrated an increase in percent of patients diagnosed via NBS, a reduced proportion of children falling into high risk nutritional categories, and decreases in PA and SA infection. Despite these improvements, malnutrition and stunting were still present with 12% of infants falling below a z score of −2 for weight and height . Distance from a CF Center has been hypothesized to influence outcomes, however, an evaluation of patients in the CFF PR who had stable addresses showed that distance from the center had no effect on FEV1pp.…”
Section: Infection Detection and Epidemiologymentioning
confidence: 99%
“…Despite these improvements, malnutrition and stunting were still present with 12% of infants falling below a z score of −2 for weight and height. 76 Distance from a CF Center has been hypothesized to influence outcomes, however, an evaluation of patients in the CFF PR who had stable addresses showed that distance from the center had no effect on FEV1pp. Interestingly, for older adults who moved further from their CF center during the time frame had higher FEV1pp, while for younger adults it worsened with increased distance.…”
Section: Epidemiologymentioning
confidence: 99%